The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s00268-001-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Metabolism during Laparoscopic Cholecystectomy: Comparison between CO2 Pneumoperitoneum and Abdominal Wall Retraction

Abstract: Recent reports have implicated CO2 pneumoperitoneum for laparoscopic surgery in the occurrence of postoperative mesenteric ischemia. With this kind of surgery, the increase in blood lactate levels has been attributed to anaerobic metabolism, probably due to tissue ischemia induced by high intraabdominal pressure (IAP). The aim of this study was to evaluate the metabolic repercussion of CO2 pneumoperitoneum during laparoscopic cholecystectomy (LC). This was a prospective randomized study of CO2 pneumoperitoneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Ortiz-Oshiro et al recently concluded that minimizing the operation time and limiting CO 2 pneumoperitoneum with 12 mmHg are important factors that protect patients undergoing laparoscopic surgery from possible perioperative ischemic phenomena. 22 Patients with cardiac and/or pulmonary diseases may respond differently to peritoneal CO 2 insufflation, even if the LC is performed under routine intra-abdominal pressure, within a short time, and adequate ventilation and oxygenation is provided. Because acidosis may develop in these patients, recurrent blood gas analysis should be done during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz-Oshiro et al recently concluded that minimizing the operation time and limiting CO 2 pneumoperitoneum with 12 mmHg are important factors that protect patients undergoing laparoscopic surgery from possible perioperative ischemic phenomena. 22 Patients with cardiac and/or pulmonary diseases may respond differently to peritoneal CO 2 insufflation, even if the LC is performed under routine intra-abdominal pressure, within a short time, and adequate ventilation and oxygenation is provided. Because acidosis may develop in these patients, recurrent blood gas analysis should be done during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an increase in lipid peroxidation products and a decrease in endogenous antioxidants were reported in the early postoperative period in laparoscopic surgery when compared to open cholecystectomy (20). It was reported that the oxidative stress contributed to the pulmonary functions impairment in laparoscopic procedures with CO 2 insufflation (19,20).…”
Section: Discussionmentioning
confidence: 94%
“…It is known that oxidative stress plays a role in the etiopathogenesis of many diseases, such as atherosclerosis, diabetes, cancer, and aging (18). Ortiz-Oshiro et al (19) suggested that the restriction of pressure by 12 mmHg and a short surgery duration are the key points to prevent potential oxidative injury in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz-Oshiro et al suggested that restriction of pressure by 12 mmHg and short surgery time are the most important factors to prevent potential oxidative injury in laparoscopic surgery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%